2015
DOI: 10.1021/acs.iecr.5b03448
|View full text |Cite
|
Sign up to set email alerts
|

Study of Simultaneous Radionuclide Sorption by Mixture Design Methodology

Abstract: The problem of simultaneous removal of Co 2+ , Sr 2+ and Cs + ions from aqueous solutions was addressed using oxide, phosphate and aluminosilicate materials from economical and abundant sources. Competition between cations was analyzed by following approaches: (i) addition of each sorbent separately to variously concentrated cation mixtures (using simplex lattice experimental design methodology), (ii) application of mixture sorbents (using extreme vertices experimental design), and (iii) consecutive addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
(122 reference statements)
1
8
0
Order By: Relevance
“…After the contamination step, the total amount of Co ions sorbed by the investigated soil was found to be 1390 mg/kg. High sorption affinities of soils and soil components toward Co are well documented [24,[30][31][32]. The sorbed amount is in agreement with the results of a previous study in which the soil from the same location was contaminated with Co under the range of experimental conditions [18].…”
Section: System Responses At Different Experimental Conditionssupporting
confidence: 90%
See 1 more Smart Citation
“…After the contamination step, the total amount of Co ions sorbed by the investigated soil was found to be 1390 mg/kg. High sorption affinities of soils and soil components toward Co are well documented [24,[30][31][32]. The sorbed amount is in agreement with the results of a previous study in which the soil from the same location was contaminated with Co under the range of experimental conditions [18].…”
Section: System Responses At Different Experimental Conditionssupporting
confidence: 90%
“…The results of a literature survey showed that different types of experimental design were used for the investigation of Co sorption by potential sorbent materials such as apatite, zeolite, bauxite residue, and dried activated sludge [23][24][25]; however, DOE approach has not been applied, to this point, for the study of Co sorption or leaching from the soil matrix. In fact, just a few examples of RSM application for the analysis of a soil remediation process can be found [26,27].…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
“…[30] However this selectivity decreases the sorption coefficient for other radionuclides on vermiculite, including 90 Sr and 241 Am, especially in the presence of 137 Cs. [32,33] 1% surface coverage of the clay with the lowest CEC (Wyoming montmorillonite: 0.76 meq/ 100 6 g) while keeping aqueous concentrations above the limit of detection (30 μCi/L). Sorbed concentrations below 1% of the CEC have previously shown not to be influenced by isotherm non-linearity, thus keeping point sorption coefficients within the linear range.…”
Section: Introductionmentioning
confidence: 99%
“…In general, solid matrices that have shown superior immobilization potential towards radioactive ions in aqueous solutions are suitable for testing in the contaminated soil. Based on the numerous investigations of the sorption affinities and capacities toward variety of radioactive pollutants, the most prominent groups of materials are aluminosilicates [73][74][75][76][77][78][79][80] and phosphates [81][82][83][84][85][86][87][88][89]. The main operating mechanisms are quite different for these two groups: while aluminosilicate addition to soil increases the number of sorption sites, phosphate materials, mainly from the apatite group, act through several removal mechanisms (ion-exchange, formation of specific surface complexes, and structural incorporation of pollutants by co-precipitation and dissolution/precipitation processes).…”
Section: Radionuclide Immobilization (Stabilization) By Soil Amendmentsmentioning
confidence: 99%